2019
DOI: 10.1093/ckj/sfy130
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the discrimination of the Kidney Donor Risk Index/Kidney Donor Profile Index scores for allograft failure and estimated glomerular filtration rate in Ireland’s National Kidney Transplant Programme

Abstract: Background The Kidney Donor Risk Index (KDRI)/Kidney Donor Profile Index (KDPI) is relied upon for donor organ allocation in the USA, based on its association with graft failure in time-to-event models. However, the KDRI/KDPI has not been extensively evaluated in terms of predictive metrics for graft failure and allograft estimated glomerular filtration rate (eGFR) outside of the USA. Methods We performed a retrospective anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 18 publications
2
8
0
Order By: Relevance
“…In general, pretransplant donor scores, such as the deceased donor score (DDS), donor risk score (DRS), SCD/ECD, and KDRI/KDPI, have limited predictive performance for graft survival. The discriminative ability (C-index) is approximately 0.6 ( 23 , 24 ). However, adding posttransplant factors, such as eGFR, proteinuria, acute rejection, and allograft histological parameters, to prediction models significantly increases prediction accuracy ( 6 ), which indicates the importance of posttransplant management.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, pretransplant donor scores, such as the deceased donor score (DDS), donor risk score (DRS), SCD/ECD, and KDRI/KDPI, have limited predictive performance for graft survival. The discriminative ability (C-index) is approximately 0.6 ( 23 , 24 ). However, adding posttransplant factors, such as eGFR, proteinuria, acute rejection, and allograft histological parameters, to prediction models significantly increases prediction accuracy ( 6 ), which indicates the importance of posttransplant management.…”
Section: Discussionmentioning
confidence: 99%
“…Our model using simple clinical features had a similar AUC of 0.69. Sexton and colleagues tested the discrimination of KDRI/KDPI for eGFR in the Ireland population, and according to the results, KDRI/KDPI was significantly associated with eGFR over 5 years but only accounted for 21% of eGFR variability over time ( 24 ). Overall, the predictive performance of using net clinical features is relatively poor.…”
Section: Discussionmentioning
confidence: 99%
“…It contains components which can increase the risk quantification score but now demonstrate comparable outcomes (e.g., DCD). Translatability of the KDRI to population cohorts outside the United States may not be valid ( 38 , 39 ). Due to disparate survival outcomes observed for kidney failure patients treated with dialysis ( 40 , 41 ) versus kidney transplantation ( 42 ) in the United States versus elsewhere, and different utilization of deceased donors (e.g., greater use of older and DCD kidneys in the United Kingdom versus the United States for example) ( 43 ), generalizability may be invalid.…”
Section: Donor Clinical Factorsmentioning
confidence: 99%
“…A recent study showed no significant difference in 5year death-censored graft survival between DCD KDPI 61-81 and DCD KDPI ≥ 85 when used for donation after cardiac death (DCD) kidneys (18). In line with the limited discriminative power regarding graft failure very high KDPI kidneys may reveal acceptable outcomes (21)(22)(23)(24). Another group showed 5-year graft survival of 91% using kidneys with KDPI score of 97% as dual transplants, highlighting that besides KDRI, nephron mass plays a major role with respect to graft survival (14,25).…”
Section: Clinical Scoresmentioning
confidence: 99%